Report on the IBS best practice visit to Sydney, N.S.W., Australia 5th-10th June 2005 - Mohd Nawawi, Norwina ([s.n.], 2005)

(untitled)
This is part of an overall report made on visit made to Sydney, Australia by CIDB team benchmarking best practices on the use of IBS in the construction industry. The visit explored the best practices of the Australian building industry on the R&D, technology, professional and vocational training and sustainable infrastructure. Output of the visit was utilised by CIDB to carve strategies aligning the existing.